Kelembagaan Informal (Gotong Royong) dalam Masyarakat Petani Padi Sawah di Desa Bhera, Kecamatan Mego - Akuilina Katarina; Hilman Apriyadin; Paulus Paji; Susanti Ebo Karakabu; Leo Sukoto (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
The informal institution of mutual cooperation (gotong royong) in the rice farming community in Bhera Village, Mego District, Sikka Regency, remains the main foundation of social solidarity and the sustainability of agricultural activities even though modernization and the use of labor have begun to shift traditional values. A qualitative approach with a case study method was used to explore the role, form, and meaning of mutual cooperation in agricultural practices. Data were collected through in-depth interviews, participant observation, and documentation studies of rice farmers who are active in mutual cooperation activities. Data analysis was carried out through reduction, presentation, and drawing conclusions using triangulation techniques to ensure the validity of the findings. The results show that mutual cooperation is manifested in every stage of farming, from uprooting seedlings, planting (planting), clearing weeds, to harvesting, which is carried out voluntarily and in turns through the Irutan Tradition system. This institution functions as a collective work mechanism that reduces production costs, overcomes labor shortages, and strengthens social ties between farmers. Beyond its economic function, mutual cooperation has profound social and cultural significance as a symbol of brotherhood, togetherness, and collective responsibility in maintaining the sustainability of local wisdom and the resilience of farming communities amidst social and technological change.